Programmed Death-Ligand 1 Expression in Non-Small Cell Lung Carcinoma Biopsies and Its Association with Tumor Infi ltrat ing Lymphocytes and the Degree of Desmoplasia - Tancoš, V; Grendár, M; Farkašová, A; Huťka, Z; Kviatkovská, Z; Plank, L (Klinicka onkologie, 2020)
BACKGROUND: Immunotherapy blocking the PD-1/PD-L1 signalling pathway has become a dominant treatment modality for patients with non-small cell lung carcinoma (NSCLC). Programmed death-ligand 1 (PD-L1) expression on the membrane of tumour cells and/or tumour infiltrating lymphocytes (TIL) evaluated immunohistochemically is still the only clinically validated predictive biomarker for immunotherapy, but it has its limitations. TIL in the tumour microenviroment was identified as having predictive value. We retrospectively evaluated 134 NSCLC resection specimens, and analysed the association between PD-L1 expression, the presence of TIL, and the degree of desmoplasia in tumours. MATERIAL AND METHODS: PD-L1 expression on tumour cells and TIL were evaluated immunohistochemically using the anti-PD-L1 antibody (clone 22C3) and the anti-CD3 antibody (polyclone), respectively. PD-L1 was scored using the “tumour proportion score” (TPS) system with three categories: TPS < 1%, 1-49%, and 50%. TIL were evaluated semiquantitatively using the “percentage of stromal TIL” (PST) system, and categories of PST < 10%, 10-49% and 50% were recorded. The association between PD-L1 expression in tumour cells and TIL was compared with the PST value. Statistical analysis was conducted using the Cochran-Armitage test, and a p-value < 5% was considered significant. RESULTS: PD-L1 expression was significantly higher in PST 10-49% and 50% categories than in the PST < 10% category in grade 1 and grade 2 adenocarcinomas (p = 0.008), grade 3 adenocarcinomas (p = 0.009), and squamous cell carcinomas (p = 0.028). PD-L1 expression in TIL was associated with the PST value in squamous cell carcinomas (p = 0.025) but not in adenocarcinomas. Desmoplastic tumours had particularly low TPS and PST values. CONCLUSION: PD-L1 expression in NSCLC is associated with the presence of TIL. Desmoplastic areas in tumours represent immunologically inactive tumour microenviroments. Administration of anti-PD-1/PD-L1 immunotherapy, together with agents blocking the TGF-β signalling pathway, represent a promising combinational therapy for patients with desmoplastic NSCLC. The authors declare they have no potential confl cts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Submitted: 25. 11. 2019 Accepted: 8. 12. 2019.
Keywords: B7-H1 Antigen; antigeny CD274; tumour infiltrating lymphocytes; Neoplasm Grading; non-small cell lung carcinoma; Lymphocytes, Tumor-Infiltrating; tumor infiltrující lymfocyty; Biopsy; nádory plic; adenokarcinom; programmed death-ligand 1; Adenocarcinoma; predictive biomarker; nemalobuněčný karcinom plic; Humans; Carcinoma, Non-Small-Cell Lung; stupeň nádoru; biopsie; Lung Neoplasms; lidé